Stand der Literatur zur operativen Steuerung von Dienstleistungsprozessen - Michael Leyer (Frankfurt School of Finance & Management, 2011)
Services are characterised by the integration of customers while the service is produced. This integration leads to interruptions in the processing of a customer order until the customer provides the missing input. Since customer behaviour can be planned to a certain extent only challenges in planning an efficient delivery of a service process arise. This holds especially true for operational control as it has to correct deviances in the short-term. Thus, the following research question occurs: How can service processes be controlled efficiently taking customer integration into account? The aim of this working paper is to conduct a comprehensive literature review with regard to the research question. The results show that the majority of approaches are originate from manufacturing dealing with processes mainly conducted by machines and having stock-keeping possibilities. These manufacturing processes and the approaches typically do not deal with the complex influence of customer integration on operational control as in the case of service processes. It is concluded that a sufficient answer to control service processes is missing so far and thus potential research areas are addressed.
Keywords: D24; L23; M11; 330; operational control; services; literature review; Dienstleistungsmanagement; Prozessmanagement; Controlling; Kundenintegration; Theorie